Galectin-3 inhibition by a small-molecule inhibitor reduces both pathological corneal neovascularization and fibrosis - Chen, Wei Sheng; Cao, Zhiyi; Leffler, Hakon; Nilsson, Ulf J.; Panjwani, Noorjahan (Investigative Ophthalmology and Visual Science, 2017)
PURPOSE. Corneal neovascularization and scarring commonly lead to significant vision loss. This study was designed to determine whether a small-molecule inhibitor of galectin-3 can inhibit both corneal angiogenesis and fibrosis in experimental mouse models. METHODS. Animal models of silver nitrate cautery and alkaline burn were used to induce mouse corneal angiogenesis and fibrosis, respectively. Corneas were treated with the galectin-3 inhibitor, 33DFTG, or vehicle alone and were processed for whole-mount immunofluorescence staining and Western blot analysis to quantify the density of blood vessels and markers of fibrosis. In addition, human umbilical vein endothelial cells (HUVECs) and primary human corneal fibroblasts were used to analyze the role of galectin-3 in the process of angiogenesis and fibrosis in vitro. RESULTS. Robust angiogenesis was observed in silver nitrate-cauterized corneas on day 5 post injury, and markedly increased corneal opacification was demonstrated in alkaline burn-injured corneas on days 7 and 14 post injury. Treatment with the inhibitor substantially reduced corneal angiogenesis and opacification with a concomitant decrease in a-smooth muscle actin (α-SMA) expression and distribution. In vitro studies revealed that 33DFTG inhibited VEGF-A-induced HUVEC migration and sprouting without cytotoxic effects. The addition of exogenous galectin-3 to corneal fibroblasts in culture induced the expression of fibrosis-related proteins, including α-SMA and connective tissue growth factor. CONCLUSIONS. Our data provide proof of concept that targeting galectin-3 by the novel, smallmolecule inhibitor, 33DFTG, ameliorates pathological corneal angiogenesis as well as fibrosis. These findings suggest a potential new therapeutic strategy for treating ocular disorders related to pathological angiogenesis and fibrosis.
Keywords: 33DFTG; Angiogenesis; Cornea; Fibrosis; Galectin